Reconstructing the Concept of Permanent Establishment in the Global Era of Significant Economic Presence - Syarif Djafar (SEAN Institute, 2026)
This research examines the reconstruction of Indonesia’s Permanent Establishment (PE) concept in response to the challenges of the digital economy. The rise of digital platforms and cross-border data transactions has diminished the relevance of the traditional PE definition, which relies on physical presence as the basis for taxation. Through a normative juridical approach, the study analyzes the inadequacy of existing regulations and explores the adoption of the Significant Economic Presence (SEP) principle as a new tax nexus. The analysis demonstrates that SEP offers a fair and modern legal mechanism to capture value creation derived from digital engagement, ensuring fiscal equity and protecting national tax sovereignty. Its effective implementation requires harmonisation between domestic law, international tax treaties, and administrative reform. The study concludes that integrating SEP into Indonesia’s taxation framework represents a necessary evolution toward a more just, adaptive, and comprehensive system suited for the digital era.